Left Main Coronary Artery Bifurcation Lesions: Two Stents vs One Stent Strategy-Comparison of Major Adverse Cardiac Events (MACE) at 2 years - Shafique, Hafiz Muhammad; Nasir, Mubarra; Samore, Naseer Ahmad; Farahe, Ali; Tariq, Muhammad Naeem; Abbasi, Muhammad Amad; Shabbir, Sadaf; Kamran, Javeria; Khan, Aleena; Azad, Naseem (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the long-term clinical results for a one-stent (1S) strategy compared to a two-stent (2S) strategy in distal unprotected left main coronary artery (ULMCA) bifurcation disease.Study Design: Comparative Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Cardiology, Rawalpindi Pakistan, from Jan 2019 to Apr 2020.Methodology: 1-S approach was defined as stenting of the main vessel only and 2-S approach as stenting side branch and main vessel. Individual undergoing LMCA intervention were included via consecutive sampling in the study. Stent Crossover approach was used in 1-S technique; whereas, DK crush, culotte, and T-stenting approaches were employed in individuals who were treated with a 2-S approach. A composite of major adverse cardiovascular event (MACE) i.e., myocardial infarction, stroke or death and target lesion revascularization (TLR) were considered as primary end-point.Results: A sum of 110 individuals were inducted, 74 of them had stenting of left main bifurcation using a 1-S approach; and 36 patients underwent a 2-S PCI. Average age of the patients included in the study was 63.9±10.8 years. In 1 stent subset, the success rate of procedure was 99% whereas 100% success rate was seen in 2-S group. During the 2-year duration of follow up,frequency of MACE in single stent subset was (5.4%) whereas it was (13.8%, p=0.253) in the 2-S subset.Conclusion: When compared to 2-S approach of distal left main stenting, a 1-S strategy appears to demonstrate optimal clinical results and 2-year survival free of MACE. Choosing appropriate interventional strategy has proven prognostically significant; so, it demands mindful approach selection.